PENGELOLAAN SARANA WISATA DI PANTAI SAKO PADANG - Pratama, Diko; Yuliana, Yuliana; Pasaribu, Pasaribu (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This article purposed to know how managing tourism facility on the coast of Sako Padang. The type of this research is descriptive with qualitative data using survey methods. The collecting technique implemented by using methods of interviewing, observation, and documentation. In this research there are three person who involved as informant using Purposive Sampling technique and five visitors using techniques of Snowball Sampling. The data analyzed in the reduction, serving data , taking the result of this research shows: 1) managing the main facility of tourism, surveillance, planning and organizing the restaurant to the future hasn’t yet exist, surveillance restaurants has been running, briefing to the restaurant hasn’t yet run completely. The parking lot is already planned but Organizing the parking does not exist. Direction and supervision of the parking lot is already running. The planning of work programmes in the management of the toilets are already commited, organizing the toilet already exists. Briefing and supervision the toilet is already running. The palacement for trash already planned. Organizing the management of trash already exist. The briefing for placement of trash already commited. Lack of supervision of the trash. 2 complementary facility of tourism management planning to the future of clean water there's already planned, organizing, and direction is running well, but supervision is still lack of attention. 3) managing secondary facility tourism in case of planning, placement for a souvenir shop there hasn’t been completed because of less budget funds, organizing is running well, direction and supervision of already implemented.Key words : managing, facility, tourism._______________________